Preliminary study on the phytoplankton of the marshes Al-Sallal , Al- Hwizah and AlÂ Chebiaysh - South Iraq - AL-Gbafily, A. A. k. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Phytoplankton flora in southern marshes of govemorate Al- Basrah ( Al-SallaJ marsh ) Meissan (Al- Hwizah marsh) and Di-qar (AlÂ Chebiaysh marsh ) were studied from August 12005 to November /2005, Four Stations were Chosen in each marsh. Identified species and total cell count were recorded . As aquality study, (35) species of algae were identified belonged to (23) genus in Al-Sallal marsh , (46) species of algae belonged (25) genus in Al-Hwizah marsh , (38) species of algae belonged (20) genus in Al-Chebiaysh marsh . The dominant species in three marshes common recorded (11) species from Bacillariophyceae belonged to (7) genus , Cyanophyceae as common recorded (3) species belonged to (3) genus , Cholorophyceae as common recorded (2) species belonged to (2) genus , Euglenophyceae as common recorded only one species . The total cell count of algae record number reached to ( 106,2 & 144,2 & 143)x I 03 cell I liter as a maximum number in marsh Al- Sallal , Hwizah and Chebiaysh respectively . Genus Phormidium recorded a high number in three marshes and all station studies